Bezier curves for solving Fredholm integral equations of the second kind - Ghomanjani, Fateme; Farahi, Mohammad Hadi; Kilicman, Adem (Hindawi Publishing Corporation, 2014)
The Bezier curves are presented to estimate the solution of the linear Fredholm integral equation of the second kind. A direct algorithm for solving this problem is given. We have chosen the Bezier curves as piecewise polynomials of degree n and determine Bezier curves on [0, 1] by n + 1 control points. Numerical examples illustrate that the algorithm is applicable and very easy to use.